Neuropsychological disorders in patients with schizophrenia and depression - Leposavić, Ivana; Dukanac, Vesna (Vojnosanitetski pregled, 2025)
Background/Aim. Neuropsychological deficits among persons with psychotic disorders are identified clinically but also through many investigations. Comparison of patients with schizophrenia and depressive patients with healthy persons showed that both groups of patients are significantly impaired on the cognitive level compared to healthy persons. The aim of this study was to compare the neuropsychological functioning between patients with schizophrenia and depressive patients with psychotic symptoms (DPS) in remission, as well as between these two groups of patients and healthy persons. Methods. The study included 90 right-handed persons divided into three groups: 30 inpatients with schizophrenia, 30 inpatients with DPS, and 30 healthy persons. For examining neuropsychological functions of all participants, the following tests were applied: Wechsler’s Individual Test of Intelligence (with subtests: Information, Digit Span, Arithmetic, Similarities, Picture Completion, Block Design, Digit Symbol), Mini-Mental State Examination, Trail Making Test, Rey-Osterrieth Complex Figure test, Hooper Visual Organization Test, phonemic, i.e., verbal fluency task, Rey Auditory Verbal Learning Test, and Wisconsin Card Sorting Test. Results. In the group of patients with schizophrenia, dysexecutive syndrome and reduced attention were singled out in several domains as basic deficits. Disturbances in abstract thinking and verbal fluency appeared together with dysexecutive syndrome, while attention disorders cause secondary damage to short-term memory, recognition in verbal modality, and information processing speed. In the neuropsychological profile of the DPS group, mild disturbances in the domain of visual search speed and information processing speed were noted. Impaired attention negatively affected the proper carrying out of other neuropsychological functions, while this phenomenon specifically impacted executive functions, visual gnosis, and processing speed among the DPS group. Conclusion. Neuropsychological disorders of patients with schizophrenia manifest in a larger number of cognitive domains and are more severe than those of the DPS group. In the DPS group, mild neurocognitive disorders were registered. Lack of motivation and effort during testing contributes to cognitive disturbances in the DPS group.